(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article reflects processes associated with monozygotic and dizygotic twins, highlighting the specific features of learning motivation that arise during educational activities. It also explores aspects of the development of motivation to avoid failure and achieve success. The article discusses motivational aspects related to the level of intelligence in twins.